Development of a real-time PCR for in vivo diagnosis of feline Borna disease - Johansson, Jonas (SLU/Dept. of Molecular Biosciences, 2004)
Borna disease virus (BDV) is the causative agent of a neurological disorder in mammals and ostriches called Borna disease. BDV is also of interest as infective agent in humans with psychiatric diseases, such as mood disorders and schizophrenia, as well as in experimental models of these diseases. In Sweden, the progressive and mostly fatal neurological disorder among domestic cats, known as staggering disease or feline Borna disease, is caused by BDV. Except for cats, natural BDV infection has also been described in horses and a free-ranging lynx in Sweden. Major clinical signs of staggering disease are staggering movement, alteration in behaviour, lumbosacral pain and inability to retract the claws. Today staggering disease is clinically suspected by excluding other reasons for clinical signs and the diagnosis is further established by examining the central nervous system histopathologically at autopsy. The diagnosis is finally confirmed by immunohistochemistry. In order to get a better clinical diagnostic tool, a duplex real-time polymerase chain reaction (PCR) assay was developed. This assay has been proven positive with different strains of BDV in infected cell lines and brain tissue samples of experimentally infected cats. Further evaluation of the new assay has to be done, such as testing the sensitivity and finding the best type of sample from the living patient. When the diagnostic method is finally evaluated it will also be essential in the evaluation of new therapies, as well as in epidemiological studies.